Incidence, etiology and timing of infections following azacitidine therapy for myelodysplastic syndromes. Issue 10 (3rd October 2017) - Trubiano, Jason A.; Dickinson, Michael; Thursky, Karin A.; Spelman, Timothy; Seymour, John F.; Slavin, Monica A.; Worth, Leon J.
Abstract: We examine the infective complications occurring during azacitidine (AZA) therapy in patients with myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML). A retrospective review of patients receiving ≥1 cycle of AZA for MDS or AML was performed. Patient demographics, infection prophylaxis/episodes and outcomes were evaluated. Sixty eight patients received 884 AZA cycles. Bacterial infections occurred in 25% of cycle-1 and 27% of cycle-2 AZA therapy. Febrile neutropenia complicated 5.3% of AZA cycles, bacteremia 2% and invasive Aspergillosis 0.3%. Using Poisson modeling, a very high IPSS-R (RR 10.26, 95% CI 1.20, 87.41, p = .033) was identified as an independent risk factor for infection. Infection-related attributable mortality was 23%. The burden of infection is high in AZA-treated patients, associated with high attributable mortality. Over 25% of AZA cycles 1 and 2 were complicated by infection, predominantly bacterial, rates dropping to <10% after cycle-5.